FDTD Analysis of a High-Sensitivity Refractive Index Sensing Based on Fano Resonances in A Plasmonic Planar Split-Ring Resonators - Mohsen Nasrolahi; Ali Farmani; Ashkan Horri; Hossein Hatami (Journal of Optoelectronical Nanostructures)
A tunable label-free refractive index biosensor based on plasmonic planar split-ring resonators is proposed. The effects of Fano resonances are studied to harness the transmission spectra in near-infrared region. In the structure, dual hexagonal ring resonators are utilized to realize the Fano resonances with the advantages of high sensitivity, large figure of merit, narrow full wave at half-maximum (FWHM), and extremely large Q-factor. Analytical and numerical outcomes display that, by slight variation of the refractive index and geometrical modes resonances can be manipulated. A high sensitivity of 1160 nm/RIU with a FoM as large as 33 is achieved. Besides, the proposed biosensor shows a relatively narrow FWHM of 50 nm, which introduces a high Q-factor of 31. Such this moderately high Q-factor ensures that the structure exhibits extreme low resonance losses that can be advantageous for high resolution detections with acceptable accuracy. Nano Fano resonance sensing is a technique used in nanophotonics for highly sensitive detection of bioanalytes. It leverages the Fano resonance effect, which arises from interference between a discrete state and a broadband continuum of states. This can lead to sharp asymmetric peaks in the absorption or scattering spectrum.